Harmony Of Political And Economic Culture In Society Development (Eurasian Journal of History, Geography and Economics, 2024)
The method of conducting business based on the market economy, the legal democratic state, the formation of the foundations of civil society, requires the further improvement of the political and economic culture of citizens. If we take a deeper approach to the issues of economic and political culture, their mutual relations have a complex content and form, and they acquire a dialectical essence. If we look at the stages of development of the state and society, we can see that the economy has always been the foundation of politics. Such a dialectical harmony indicates that the issue was only viewed from one side. This situation is particularly aggravated during the former Shura period. Because, during this period, the economy was turned into a tool of politics based on a single administration. It is a historical fact that cultural issues, in particular, humanistic requirements and norms, must be taken into account in relations related to the economic development of society. This shows that culture is inextricably linked with production and economic development. Otherwise, human moral relations in society will deteriorate, and alienation between people will increase. This, in turn, can lead to socio-economic decline. Some people claim that in the conditions of a free market economy, culture and spirituality will become secondary, and spiritual poverty will increase. Such a contrast between a free market economy and culture is absolutely inappropriate; on the contrary, they complement each other, because only a highly culturally healthy, strong society will be ready for economic reforms